Successful Mechanical Thrombectomy for Acute Ischemic stroke beyond the Thrombolysis Window - Phuyal, Subash; Adhikari, Rupendra Bahadur (Grande Medical Journal, 2025)
A 70-year old male patient was referred from another hospital to our emergency department with sudden onset right sided weakness and inability to speak. The last known well time was approximately 7 hours prior to presentation. On arrival, the patient was hemodynamically stable. Neurological examination revealed dense right hemiparesis and global aphasia, with a National Institutes of Health Stroke Scale (NIHSS) score of 13, consistent with a moderate to severe acute ischemic stroke. The patient was immediately shifted to the catheterization laboratory for mechanical thrombectomy. Final angiography demonstrated complete reperfusion with Thrombolysis in Cerebral Infarction (TICI) grade 3 flow.